1962
DOI: 10.1161/01.res.11.3.370
|View full text |Cite
|
Sign up to set email alerts
|

Functional Sympatholysis During Muscular Activity

Abstract: The effects of both direct and reflexly induced increases in sympathetic activity on the blood flow to an extremity at rest and during muscular activity have been studied. When the O 2 uptake of an extremity is increased during muscular activity, its vascular resistance falls sharply with a small increase in O 2 uptake and thereafter declines only slightly. The responsiveness of a vascular bed to adrenergic stimulation diminishes sharply with a small increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
160
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(171 citation statements)
references
References 24 publications
11
160
0
Order By: Relevance
“…48 In contrast, during dynamic exercise, sympathetic stimulation evokes an increase in cardiac output, but the BP is only moderately elevated due to the fall in peripheral resistance as a result of local muscle vasodilatation (described in the literature as 'functional sympatholysis'). 49 In this study, during the FHG the decrease in the T i was accompanied by a decrease in the PPP/CPP, Table 4 Haemodynamic parameters during dynamic KE exercise (n ¼ 14) Central stiffness during mental stress and exercise C Lydakis et al indicating that the augmentation in the CPP was greater than that observed in the periphery. In the dynamic protocol the T i was also decreased (indicating increased central AS), but the PPP/CPP ratio did not decrease but rather showed a small (but not significant) rise towards the end of exercise.…”
Section: Lydakis Et Almentioning
confidence: 48%
“…48 In contrast, during dynamic exercise, sympathetic stimulation evokes an increase in cardiac output, but the BP is only moderately elevated due to the fall in peripheral resistance as a result of local muscle vasodilatation (described in the literature as 'functional sympatholysis'). 49 In this study, during the FHG the decrease in the T i was accompanied by a decrease in the PPP/CPP, Table 4 Haemodynamic parameters during dynamic KE exercise (n ¼ 14) Central stiffness during mental stress and exercise C Lydakis et al indicating that the augmentation in the CPP was greater than that observed in the periphery. In the dynamic protocol the T i was also decreased (indicating increased central AS), but the PPP/CPP ratio did not decrease but rather showed a small (but not significant) rise towards the end of exercise.…”
Section: Lydakis Et Almentioning
confidence: 48%
“…During exercise, sympathetic vasoconstriction is diminished in the active muscles but preserved in the inactive muscles (65,87). This regional selectivity indicates that, akin to the intrinsic coupling between muscle fiber recruitment and blood flow described in the introduction, functional sympatholysis is mediated by local events that are confined to the active muscles and not by humoral factors carried in the systemic circulation (Fig.…”
Section: Mechanisms Underlying Functional Sympatholysismentioning
confidence: 81%
“…As early as 1930, Rein (64) reported that reflex activation of sympathetic nerves decreased blood flow to a greater extent in resting vs. exercising dog hindlimb. In 1962, Remensnyder et al (65) coined the term "functional sympatholysis" to describe the markedly reduced vasoconstrictor responses that they observed in exercising muscle in response to activation of sympathetic nerves or local intra-arterial infusion of norepinephrine. However, perusal of the literature indicates that functional sympatholysis has not been a consistent finding.…”
Section: Is Sympathetic Vasoconstriction Modulated In Exercising Muscle?mentioning
confidence: 99%
“…An attenuation of vasoconstriction in the arterial vasculature of skeletal muscle during muscle contraction has been reported by a number of investigators (8,22,23,36,37,42). This diminished vascular responsiveness to sympathetic stimulation during muscular contraction was termed "functional sympatholysis" by Remensnyder et al (36). Recently, studies by Thomas and colleagues (12,38,40,41) have provided evidence that the mechanism by which sympatholysis occurs is related to the production of nitric oxide.…”
mentioning
confidence: 93%
“…Indeed, it has been argued that, as exercise intensity increases, sympathetic vasoconstriction in active skeletal muscle also increases (34). An attenuation of vasoconstriction in the arterial vasculature of skeletal muscle during muscle contraction has been reported by a number of investigators (8,22,23,36,37,42). This diminished vascular responsiveness to sympathetic stimulation during muscular contraction was termed "functional sympatholysis" by Remensnyder et al (36).…”
mentioning
confidence: 98%